New Business Creation An International Overview - Reynolds, Paul D.; Curtin, Richard T.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Understanding the origins of new businesses$1 (Bthe firm creation process$1 (Bhas been dramatically affected by the development of longitudinal studies of business start-ups. Several projects have been implemented to track the development of new firms, from the emergence of a business idea and organization of a start-up team through the birth of an operational business. The U.S. projects (the first and second Panel Studies of Entrepreneurial Dynamics, known as PSED I and II) have counterparts in a number of other countries: Australia, Canada, China, Latvia, Netherlands (two projects), Norway, and Sweden. These eleven projects in nine countries, implemented over the past decade, are at different stages of development and have been utilized for a wide range of assessments of entrepreneurial and business creation phenomena. This volume presents the state of the art of these international research projects, providing the first in-depth comparison of the firm creation data across a wide range of national contexts. The work will be of great interest to the research community, particularly those developing such projects in their own countries, as well as policy makers and scholars interested in the effect of national context on the business creation process.s
Keywords: Economics; Entrepreneurship; Economics/Management Science; Entrepreneurship; Business/Management Science, general; Industrial and Organisational Psychology